"Bangsawan prampoewan"; Enlightened Peranakan Chinese women from early twentieth century Java - Kwartanada, Didi (Wacana, Journal of the Humanities of Indonesia, 2017)
The end of the nineteenth century witnessed paradox among the Chinese in colonial Java. On one hand, they were prospering economically, but were nonetheless held in contempt by the Dutch, encountered legal discrimination and faced challenges if they wanted to educate their children in European schools. Their marginal position motivated them do their utmost to become "civilized subjects", on a par with Europeans, but they were also inspired to reinvent their Chinese identity. This contribution will highlight role played by "enlightened" Chinese, the kaoem moeda bangsa Tjina. Central to this movement were the Chinese girls known to the public as bangsawan prampoewan (the noblewomen), who wrote letters the newspaper and creating a gendered public sphere. They also performed western classical music in public. Considering the inspirational impact of bangsawan prampoewan's enlightening achievements on non-Chinese women, it is appropriate to include them into the narrative of the history of the nation's women's movements.